The feasibility study on creation of freight village in Hormozgan Province - Afandizadeh, Shahryar; Moayedfar, Reza (Transport, 2008)
The purpose of the present study is to study the feasibility of creating a freight village (multimodal terminal) in patronage grounds of the special economic zone of Shahid Rajaie port in Hormozgan Province. To do so, first, some explanations have been presented in terms of familiarization and study of a freight village and its structural models in different countries of the world. Then, the current status of patronage grounds in the special economic zone of Shahid Rajaie port has been studied. Therefore, the proposed models for the special economic zone of Shahid Rajaie port have been implemented and have undergone sensitivity analysis, and finally the results of the analyses and the assessment of different options of sensitivity analysis on the present parameters in the model have been presented. First published online: 27 Oct 2010